Sistem Penentu Penilaian Siswa pada Kurikulum 2013 Menggunakan Algoritma Simple Additive Weighting (SAW) (Studi Kasus SDN Darmaga V Subang) - Anderias Eko Wijaya; Dadan Marwan (Maranatha University Press, 2016)
The Curriculum of 2013 form students to conduct an observation, questioning and reasoning toward the lesson/ science which is taught. Students are given the subjects based on the theme that is integrated in order to have knowledge of the environment, life, and have a strong personal foundation in social life and had a better creativity. Teacher as a spearhead in the implementation of the curriculum supposedly able to draw on the curriculum of 2013 precisely in term of the process of assessment to improve students’ competencies and furthermore it is expected to improve the quality of its graduates who are able to face the global challenge. In order to have an accurate assessment therefore it is needed / demanded a system to support an assessment decision by using Simple Additive Weighting method (SAW). Simple Additive Weighting method (SAW) is well-known as a weighted summation method.The basic concept of Simple Additive Weighting (SAW) is looking at every alternative of weighted sum of all attributes. Simple additive weighting (SAW) method requires the normalization process of matrix (X) to a scale that can be compared with all the alternative ratings which is exist.This the system is built by using PHP programming language and DBMS MySQL. Keywords — DBMS MySQL, Kurikulum 2013, PHP, Simple Additive Weighting.